Forecasting Employment for Germany - Darius Hinz; Camille Logeay (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2006)
This paper deals with the estimation of employment equations for Germany, which are to be used for forecasting and simulation purposes. The authors estimate both single and system error correction equations for German working hours using quarterly raw data covering the period 1980:1-2004:2. Since the focus is on the question whether German reunification has affected or even modified the underlying economic relationships, the authors compare the results to those reported in previous studies for West Germany and Germany, respectively. The authors find that the elasticity of employment with respect to output is robustly estimated and can therefore be restricted to one. The elasticity of employment with respect to the real wage, however, is affected by German reunification and relative factor prices no longer play a significant role. The forecasting quality of the employment equation is satisfactory.
urn:nbn:de:101:1-20080814124
Keywords: E24; E27; C22; C32; C53; 330; employment; forecasting; cointegration; Germany